Peer Relatedness, School Satisfaction, and Life Satisfaction in Early Adolescence: A Non-recursive Model - Gempp, René; González-Carrasco, Mònica (Frontiers in Psychology, 2021)
Cumulative evidence suggests that, for children and adolescents who spend most of their time at school, peer relatedness is an essential component of their overall sense of belonging, and correlates with subjective well-being and school-based well-being. However, it remains unclear what the underlying mechanism explaining these relationships is. Therefore, this study examines whether there is a reciprocal effect between school satisfaction and overall life satisfaction (Hypothesis 1), and whether the effect of peer relatedness on life satisfaction is mediated by school satisfaction (Hypothesis 2). A nonrecursive model with instrumental variables was tested with econometric and structural equation modeling methodologies, using a cross-sectional sample of n = 5,619 Chilean early adolescents (49.2% girls), aged 10, 11, and 12 years (46.13%, 44.99%, and 8.88% respectively). Results were highly consistent across methods and supported the hypotheses. First, the findings confirmed a significant reciprocal influence between school satisfaction and overall life satisfaction, with a greater impact from school to life satisfaction. Second, the effect of peer relatedness on overall life satisfaction wall fully mediated by school satisfaction. The study further suggests the importance of considering reciprocal effects among domain-specific satisfaction and overall life satisfaction and illustrates the application of nonrecursive models for this purpose.